A combined 3D-SIM/SMLM approach allows centriole proteins to be localised with a precision of ~4-5nm - Gartenmann, L; Wainman, A; Qurashi, M; Kaufmann, R; Schubert, S; Raff, J; Dobbie, I (Cell Press, 2017)
Centrioles are small barrel-shaped structures that form centrosomes and cilia [1]. Centrioles assemble around a central cartwheel comprising the Sas-6 and Ana2/STIL proteins. The amino termini of nine Sas-6 dimers form a central hub of ∼12 nm radius from which nine dimer spokes radiate, placing the Sas-6 carboxyl termini at the outer edge of the ∼60 nm radius cartwheel [2]. Several centriole proteins are distributed in a toroid around the cartwheel, and super-resolution light microscopy studies have measured the average radii of these ∼100–200 nm radius toroids with a ‘precision’ — or standard deviation (s.d. or 1σ) — of ±∼10–40 nm. The organization of Ana2/STIL within the cartwheel, however, has not been resolvable. Here, we develop methods to calculate the average toroidal radius of centriolar proteins in the ∼20–60 nm range with a s.d. of just ±∼4–5 nm, revealing that the amino and carboxyl termini of Ana2 are located in the outer cartwheel region.